Assessing Education for Sustainable Development (ESD) Competencies and Environmental Empathy in Disaster and Environment Knowledge to Support SDGs 2030 - Windi Asnita Sari; Wiwit Artika; Rina Suryani Oktari; Safrida; Hafnati Rahmatan; Daisuke Sasaki (Jurnal Pendidikan IPA Indonesia, 2025)
Education for Sustainable Development (ESD) plays a crucial role in achieving the Sustainable Development Goals (SDGs) 2030 by promoting the acquisition of understanding, knowledge, and skills. This study aims to assess students’ Education for Sustainable Development (ESD) competencies and examine the correlation between ESD competency and students’ environmental empathy in Disaster and Environmental Knowledge at Universitas Syiah Kuala. This study employed a correlation research method with quantitative and qualitative approaches using random sampling techniques. The random sampling method was used to select 339 participants with a 95% confidence level. Data were collected using an ESD competency test, an environmental empathy questionnaire, and interviews. Data analysis was performed using the Pearson product-moment correlation technique. The analysis results show that the average score for students’ systems thinking competency was 73.67% (good category), and students’ critical thinking competence was 71.64% (adequate category). Statistical analysis shows a significant positive correlation between ESD competency and environmental empathy (r = 0.301), indicating that ESD competency explains 31.1% of the variance in environmental empathy. Therefore, it can be concluded that ESD competency is positively related to environmental empathy, though with a low level of correlation. This study provides valuable insights for universities and stakeholders in designing more effective ESD programs to promote sustainable development, especially goals 4 (quality education) and 13 (climate action).